Thermodynamic cycle design of a 700W@3K sub-cooled helium refrigerator test facility. (April 2019) - Lu, X. F.; Zhang, Q. Y.; Zhou, Z. W.; Zhu, Z. G.; Chen, A. Y.; Fu, B.; Li, S. S.
Abstract: In order to increase the magnetic field and temperature margin of superconducting magnets, a test facility for a 3K sub-cooled helium refrigerator was proposed to decrease the operation temperature from the saturated helium to the sub-cooled helium. The process flow of 3K sub-cooled helium refrigerator has been analysed, including the 4.5K refrigerator unit and 3K refrigerator unit. Two cold compressors arranged in series have been adapted to decompress pressure to achieved 3K sub-cooled helium. The thermodynamic cycle of the 3K sub-cooled helium refrigerator have been designed, which can provide 2.5kW@4.5K in 4.5K mode or 1.2KW@4.5K + 700W@3K in 3K mode. As the most important port, the design parameters and mechanical test at normal temperature test of cold compressors were shown.